Analysis of the Effect of Perceived Service Quality and Perceived Value on E Loyalty Through Customer Satisfaction and Customer Trust as Intervening Variables: Study on Wardah Beauty Products e-Commerce Consumers in Semarang City - Sindi Clarista Efendi; I Made Bayu Dirgantara (International Journal of Science and Society, 2023)
This research aims to analyze the influence of perceived service quality and perceived value on e-loyalty through customer satisfaction and customer trust as intervening variables on e-commerce consumers of Wardah beauty products in Semarang City. The research population was all consumers who purchased Wardah products online through the 5 largest e-commerce sites in Indonesia and a sample of 100 consumers. The data analysis method is path analysis with Smart Partial Least Square (PLS). This research produces findings that there is a positive influence of perceived value, customer satisfaction, customer trust on e-loyalty but perceived service quality has no effect on e-loyalty. There is a positive influence of perceived service quality and perceived value on customer satisfaction, while customer satisfaction has a positive influence on customer trust. There is an indirect influence of perceived service quality on e-loyalty through customer satisfaction. There is an indirect influence of perceived value on e-loyalty through customer satisfaction. There is an indirect influence of customer satisfaction on e-loyalty through customer trust.